1999
DOI: 10.1016/s0022-2275(20)32149-0
|View full text |Cite
|
Sign up to set email alerts
|

13-(S)-Hydroxyoctadecadienoic acid (13-HODE) incorporation and conversion to novel products by endothelial cells

Abstract: 13(S)-Hydroxy-[12,13-3 H]octadecadienoic acid (13-HODE), a linoleic acid oxidation product that has vasoactive properties, was rapidly taken up by bovine aortic endothelial cells. Most of the 13-HODE was incorporated into phosphatidylcholine, and 80% was present in the sn -2 position. The amount of 13-HODE retained in the cells gradually decreased, and radiolabeled metabolites with shorter reverse-phase high-performance liquid chromatography retention times (RT) than 13-HODE accumulated in the extracellular fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…WLS black-boned chickens showed higher levels of linoleic acid oxidation product, 13-HODE and lower levels of phosphatidylcholine in breast muscle compared with the two white muscled chicken breeds. Fang et al [ 19 ] indicated that 13- HODE has vasoactive properties, was rapidly taken up by bovine aortic endothelial cells. 13-HODE prevents cell adhesion to endothelial cells and can inhibit cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…WLS black-boned chickens showed higher levels of linoleic acid oxidation product, 13-HODE and lower levels of phosphatidylcholine in breast muscle compared with the two white muscled chicken breeds. Fang et al [ 19 ] indicated that 13- HODE has vasoactive properties, was rapidly taken up by bovine aortic endothelial cells. 13-HODE prevents cell adhesion to endothelial cells and can inhibit cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…HODEs, as with HETEs, are generally present in healthy pregnancies [ 21 ]; they function as PPAR ligands and have atherogenic properties. HODE activity is modulated by Th1 and Th2 lymphocytes with cytokine and chemokine participation, either pro- or anti-inflammatory, depending on the type of lymphocytes present [ 31 ]. Best et al demonstrated that maternal 13-HODE significantly decreases throughout normal pregnancy, suggesting that less metabolite is transferred to the developing fetus [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…As these eicosanoids are associated with pro-inflammatory effects, this finding seems contradictory at first. However, this finding is explainable by LOX pathway activation by IL4 [ 49 , 65 , 66 , 67 , 68 ], which we used to polarize M2 macrophages. In the future, other M1/M2 macrophage differentiation approaches as well as the analysis of primary M1/M2 macrophages will allow confirmation of these findings.…”
Section: Discussionmentioning
confidence: 99%